Necesidad de codificar la devolución del pago indebido de pensiones alimenticias cuando científicamente se ha demostrado no ser padre. y en la demanda se ha fijado la pensión provisional de alimentos, “ineludible reforma” - Velásquez Velásquez, Denni Nurisnarda (2015)
In the Ecuador it has become habit of the society outlining judicial demands of legal foods against who doesn't have the legal obligation of the benefit of legal foods. As we know the right of legal foods in our juridical ordainment it is a personal right or credit that it is born of the law, and it is based in the bond parento-branch that is the relationship bond between parents and children, the same one that expands to the grandparents, uncles and siblings that are those denominated forced subsidiary. The filiation bond is verified by means of the scientific tests of DNA that have a grade of certainty of 99, 99%, and they settle down if the suitable bond exists between the alimentary one and the defendant (legal feeder). With the last reformation to the Title V Of the Right to Foods Of the Book Second of the Code of the Childhood and Adolescence, for the Reformatory Law published in the R.O. Number 643 of the day Tuesday July of 2009, 28 the same one that in their third article unnumbered, it establishes that the right of legal foods doesn't admit refund of that paid, that which prevents the defendant to request the refund of the undue payment of feeding pensions. In the normative one effective although it has been tried to aid the rights of the alimentary one (children, girls and adolescents), the ability has not settled down of requesting the refund of the paid pensions unduly, this is when it is demonstrated that between the alimentary one and the defendant bond filial parento doesn't exist, that which constitutes juridical insecurity, because a person doesn't should without there is not licit cause in the obligation, and when not existing filiation bond, neither obligation exists of lending the legal foods. With the new judicial procedure established by the suitable Reformatory Law, the foods are owed from the presentation of the demand and the Judge of the Family, Woman, Childhood and Adolescence to the moment to qualify her fix the provisional pension, the same one that you get paid for personal urgency. For the suitable reasons it is necessary to reform the Code of the Childhood and Adolescence, establishing the refund of that paid unduly by concept of legal foods, and to establish the responsibility for damages and damages against the actore of the demand if it is proven that it has worked with recklessness and bad faith. It is necessary to emphasize that the figure of the refund exists in the Civil Code, but to the being the Code of the Childhood and Adolescence, a legal body of superior hierarchy, the no admission of refund of the already prevails paid by legal foods, for what is of urgency to reform the Code of the Childhood and Adolescence. A very important aspect that should be analyzed with object of outlining an appropriate reformation to the Organic Code of the Childhood and Adolescence, is that the juridical, included obligations that of foods, is born of the law to be completed a logical and normative precept, to this respect it should be kept in mind that the obligation of foods is born of the bond parento-branch, that is to say the legal or natural knot of relationship between parents and children, or with the other ones forced subsidiary as it determines them the same Code in mention. If the demand has been outlined with deceit, to obtain a type of economic entrance in the defendant's damage, the ability should settle down of reimbursing the unduly paid, because if filiation bond doesn't the obligation it exists, and this is something that with the current one normative you cannot claim. The Civil Code if it establishes a refund action and of sanction with the compensation of damages and damages, but when being in inferior hierarchy that the Organic Code of the Childhood and Adolescence, it cannot think about this action that has valid foundation in the principle of juridical security and in the foundation of the foods obligations that is the filiation or the relationship